Typological analysis of slidequakes emitted from landslides: experiments on an expander body pile and Sobradinho landslide (Brasilia, Brazil) - Hussain,Yawar (2019)
Abstract Reactivation of a landslide is usually accompanied by microseismic signals emitted from the deforming soil mass. The reproduction of similar signals in a physical model test conducted under control conditions can allow researchers to explore and test such complicated signals to improve the prediction of full-scale failure. The present study investigates the similarity between the slidequakes (microseismicity) naturally emitted from an existing colluvial landslide (Sobradinho, Brazil) in response to rainfalls and the emissions generated by a pullout test of an expander body (EB) pile in tropical soil under controlled conditions. The microseismic signals emitted from both experimental sites (i.e. the landslide and the EB pile test) were recorded and compared. Data were acquired by mini-arrays of four short-period seismometers. For the signal nomenclature, a typological scheme was adopted, in which sonograms/spectral contents of the signals were used. As a result, short duration microseismic signals were observed during the pullout test. In contrast, at the Sobradinho landslide, the testing detected signals of different characteristics whose source mechanisms have remained ambiguous, mainly because of the short duration of the data campaigns. However, at the landslide, propagating events were observed that might be attributed to the energies generated by the river bedload during the heavy rains. The present study offers some insight into the pre-collapse dynamic behavior of unstable slopes in clayey formations.